2014
DOI: 10.17221/7587-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DGAT1 polymorphisms on the estimated breeding values of Czech Simmental sires

Abstract: ABSTRACT:The aim was to evaluate the effect of polymorphisms in the promoter and in the coding region of the DGAT1 gene on the estimated breeding values (EBV) of Czech Simmental sires. The K232A polymorphism (n = 191) in the coding region was genotyped by PCR/RFLP, and the KU and SA polymorphisms in the promoter (n = 203) were identified in an automatic sequencer. In the K232A polymorphism, the frequency of the genotype AA (Alanine) was greater than that of the genotype KA, the homozygous genotype KK (Lysine) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
3
1
0
Order By: Relevance
“…The effects of the genotypes on lactation traits showed that in crossbred Holstein the KA genotype had a significantly higher fat content than the AA genotype (P <0.05) (Table 2). These results were in accordance with the findings of other authors (Molee et al 2012, Hanusova et al 2014, Kadlecova et al 2014) who reported that the K allele is responsible for variations in the amount of milk fat.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The effects of the genotypes on lactation traits showed that in crossbred Holstein the KA genotype had a significantly higher fat content than the AA genotype (P <0.05) (Table 2). These results were in accordance with the findings of other authors (Molee et al 2012, Hanusova et al 2014, Kadlecova et al 2014) who reported that the K allele is responsible for variations in the amount of milk fat.…”
Section: Resultssupporting
confidence: 93%
“…In both groups, regarding DGAT1 gene, the genotype KA prevailed over both homozygous genotypes with allele K as less frequent (Table 1). The results from the current study differed from those reported in a previous study for the Simmental breed, where the frequency for the allele K was 0.055 (Hanusova et al 2014). Results for crossbred Holstein were in accordance with earlier findings (0.36) (Molee et al 2012) and Holstein (0.28) (Kadlecova et al 2014).…”
Section: Resultssupporting
confidence: 74%
“…But there are opportunities to use clinical diseases in addition to predictor traits and genomic information to strengthen genetic evaluations for metabolic health in the future. The analysis of the relationship between polymorphic genes and EBVs for milk performance (Table 3) showed that DGAT1 was significant consistently with the previous observations by Grisart et al (2002) and Hanusova et al (2014). The GC/GC genotype (GC coding for alanine) was associated with high milk yield like in the previous reports.…”
Section: Resultssupporting
confidence: 85%
“…The gene diacylglycerol-O-transferase 1 (DGAT1) is mapped in the centromere region of BTA14 and encodes the diacylglycerol-O-transferase enzyme which catalyses the final step in triglyceride synthesis (Grisart et al, 2002). The allele frequencies and effects of polymorphic variants of DGAT1 gene have been characterized in many dairy cattle population: in New Zealand (Spelman et al, 2002), Germany (Thaller et al, 2003), France (Gautier et al, 2007), Italy (Scotti et al, 2010), Czech Republic (Hanusova et al, 2014) and many other countries. In dairy cows, DGAT1 gene is considered to be a candidate gene for milk fat content.…”
Section: Introductionmentioning
confidence: 99%